Downregulation of TNF-α/TNF-R1 Signals by AT-Lipoxin A4 May Be a Significant Mechanism of Attenuation in SAP-Associated Lung Injury - Suhui Yu; Jianming Xie; Yukai Xiang; Shengjie Dai; Dinglai Yu; Hongwei Sun; Bicheng Chen; Mengtao Zhou (Mediators of Inflammation)
Our previous studies verified the potent anti-inflammatory effects against severe acute pancreatitis (SAP) of AT-Lipoxin A4 and their analogues. However, the anti-inflammatory effects of AT-Lipoxin A4 on SAP-associated lung injury are not thoroughly known. We used western blot, polymerase chain reaction (PCR), and immunofluorescence to investigate the downregulation of TNF-α signals in cellular and animal models of SAP-associated lung injury following AT-Lipoxin A4 intervention. In vitro, we found that AT-Lipoxin A4 markedly suppressed protein expression in TNF-α signals in human pulmonary microvascular endothelial cell, such as tumor necrosis factor receptor-associated factor 2 (TRAF2), TNF-R1-associated death domain (TRADD), receptor-interacting protein (RIP), vascular cell adhesion molecule-1 (VCAM-1), and E-selectin. Moreover, AT-Lipoxin A4 inhibited downstream signals activated by TNF-α, including NF-κB/p65, JNK/MAPK, and ERK/MAPK. In vivo, AT-Lipoxin A4 significantly decreased pathological scores of the pancreas and lungs and the serum levels of IL-6 and TNF-α. Immunofluorescence, western blotting, and real-time PCR assay showed that AT-Lipoxin A4 significantly attenuated the expression of TNF-R1, TRADD, TRAF2, and RIP in the lungs of SAP rats. In addition, the activation of NF-κB was also downregulated by AT-Lipoxin A4 administration as compared with SAP rats. AT-Lipoxin A4 could inhibit the production of proinflammatory mediators and activation of TNF-α downstream signals such as NF-κB and MAPK. Downregulation of TNF-α signals by AT-Lipoxin A4 may be a significant mechanism in the attenuation of SAP-associated lung injury.